The Innovative Approach to Risk Management as a Part of Destination Competitiveness and Reputation - Marica Mazurek (Communications - Scientific letters of the University of Zilina, 2020)
The aim of this paper is a critical discussion on application of a framework for tourism disaster management and the response of governments and communities to crises and disasters. Perception of danger and threat might be decisive factors, which could undermine image, reputation, and competiveness of a country. It might have also a decisive influence on the performance of a country from the economic point of view and especially influence on service provisions, for instance infrastructure (transportation), safety and security. The conceptual approach to research is based on analysis and discussion of the applied models of crisis management in tourism. Main purpose of this paper is to overview and compare methodological and conceptual approaches of academics to crises and disasters in published articles dealing with the creation of pro-active risk management models and their application.